A previously undescribed phenylethanoid glycoside from Callicarpa kwangtungensis Chun acts as an agonist of the Na/K-ATPase signal transduction pathway. (January 2021) - Xu, Yunhui; Jiang, Xueyang; Xu, Jian; Qu, Wei; Xie, Zijian; Jiang, Ren-Wang; Feng, Feng
Abstract: The new concept that Na/K-ATPase acts as a receptor prompted us to look for new ligands from Callicarpa kwangtungensis Chun. Using column chromatography, an undescribed phenethyl alcohol glycoside, callicarpanoside A, and an undescribed benzyl alcohol glycoside, callicarpanoside B, along with twelve known polyphenols were isolated from Callicarpa kwangtungensis Chun. All the isolated compounds were evaluated for their Na/K-ATPase (NKA) inhibitory activities. Using our NKA technology platform-based screening assay protocols, callicarpanoside B was identified as an undescribed Na/K-ATPase agonist. In particular, the newly identified benzyl alcohol glycoside was found to bind NKA and activate the receptor NKA/Src complex, resulting in the activation of protein kinase cascades. These cascades included extracellular signal-regulated kinases and protein kinase C epsilon, as well as NKA α1 endocytosis at nanomolar concentrations. Unlike the class of cardiotonic steroids, callicarpanoside B showed less inhibition of NKA activity and caused less cellular toxicity. Moreover, callicarpanoside B was found to bind NKA at a different site other than the cardiotonic steroids binding site. Thus, we have identified an undescribed NKA α1 agonist that may be used to enhance the physiological processes of NKA α1 signaling. Graphical abstract: Image 1 Highlights: Two new compounds along with 12 known polyphenols were isolated from Callicarpa kwangtungensis. Callicarpanoside B was identified as an undescribed agonist of the Na/K-ATPase signal transduction pathway. Callicarpanoside B binds NKA at a distinct site other than the CTS binding site.